(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This research paper consists of effects of earthquake force and wind force on tubular tower Structure with different bracing system such as invert ‗V‘ bracing and ‗X‘. The Indian standard code of practice IS-1893 (Part I 2002), IS-8751987 (PartIII), IS-800-2007 guidelines and methodology are used to analyze the tower structure. Etab2015 structural analysis software is used to analyze the tower under the effect of earthquake forces and wind forces in zone III. Seismic analysis done by Response Spectrum Analysis. The behaviour of tower was examined and compared on the basis of displacement and base shear.